PENGARUH PENGHINDARAN PAJAK DAN PROFITABILITAS TERHADAP COST OF DEBT PADA PERUSAHAAN SUB SEKTOR TEKSTIL DAN GARMEN YANG TERDAFTAR DI BEI 2016-2019 - Mayer Nicolas Hendryanto Pardosi; Romulo Sinabutar (Fakultas Ekonomi Universitas Advent Indonesia, 2021)
Cost of debt or cost of debt is an obligation that is owned by a company and that must be paid against its debts. This study aims to determine the effect of tax avoidance and profitability on the cost of debt in textile and garment sub-sector companies listed on the Indonesia Stock Exchange. This study used 40 research samples from 10 textile and garment sub-sector companies with company codes, namely: BELL, INDR, PBRX, POLY, RICY, SRIL, SSTM, TRIS, UNIT, ESTI from 2016-2019. This type of research is quantitative research. The independent variable (X1) is tax avoidance, (X2) is profitability, while the dependent variable (Y) is cost of debt. Researchers used descriptive statistics, correlation coefficient, coefficient of determination, significant F test, significant T test, and linear regression analysis (simple) as data analysis. The results of the research that the researchers have done show that there is no significant effect between tax avoidance on the cost of debt. The results of this study also show that there is a significant influence between profitability and cost of debt.